Integration of state of health in power management algorithms for hybrid renewable energy systems - Siddharth Joshi; Akash Barva; Digesh D. Shah (Transactions on Energy Systems and Engineering Applications, 2026)
This paper proposes a State of Health (SOH)—aware power management framework for a hybrid renewable energy system integrating solar photovoltaic, wind energy, and battery energy storage systems. Unlike conventional strategies that rely solely on State of Charge, the proposed approach embeds SOH as an active control variable within the power management algorithm to adapt battery dispatch based on degradation state. Real-world solar and wind datasets, along with experimentally obtained battery degradation data, are used for system evaluation. Simulation results demonstrate that incorporating SOH reduces battery stress, limits excessive cycling under degraded conditions, and improves long-term system reliability. The proposed framework enables lifecycle-aware energy management, enhancing the sustainability and operational resilience of hybrid renewable energy systems.